Urinary oxytocin positively correlates with performance in facial visual search in unmarried males, without specific reaction to infant face - Saito, Atsuko; Hamada, Hiroki; Kikusui, Takefumi; Mogi, Kazutaka; Nagasawa, Miho; Mitsui, Shohei; Higuchi, Takashi; Hasegawa, Toshikazu; Hiraki, Kazuo (Frontiers in Neuroscience, 2014)
The neuropeptide oxytocin plays a central role in prosocial and parental behavior in non-human mammals as well as humans. It has been suggested that oxytocin may affect visual processing of infant faces and emotional reaction to infants. Healthy male volunteers (N = 13) were tested for their ability to detect infant or adult faces among adult or infant faces (facial visual search task). Urine samples were collected from all participants before the study to measure the concentration of oxytocin. Urinary oxytocin positively correlated with performance in the facial visual search task. However, task performance and its correlation with oxytocin concentration did not differ between infant faces and adult faces. Our data suggests that endogenous oxytocin is related to facial visual cognition, but does not promote infant-specific responses in unmarried men who are not fathers.